Odpowiedzi

2010-03-22T19:07:20+01:00
A)6(x+y)=10y
y-x=0,5

6x+6y = 10y
y = 0,5+x

6x+6*(0,5+x) = 10*(0,5+x)
6x+3+6x = 5+10x /-10x -3
2x = 2 /:2
x = 1

y = 0,5+x
x = 1
y = 1,5

b)10(y+2)+3(x-5)=x-5
25(y+2)+3(x-5)=-10

10y+20+3x-15 = x-5
25y+50+3x-15 = x-5

10y+2x = -10 /:2
25y+2x = -40

5y+x = -5
25y+2x = -40

x = -5y-5
25y+2*(-5y-5) = -40

25y-10y-10 = -40
x = -5y-5

15y = -30
x = -5y-5

y = -2
x = -5*(-2)-5

y = -2
x = 5



c)2(2x-y)+3(x+3y)=42
5(x+3y)-8(2x-y)=-32

4x-2y+3x+9y = 42
5x+15y-16x+8y = -32

7y+7x = 42 /:7
23y-11x = -32

x+y = 6
23y-11x = -32

x = 6-y
23y-11x = -32

23y-11*(6-y) = -32
x = 6-y

23y-66+11y = -32 /+66
x = 6-y

34y = 34
x = 6-y

y = 1
x = 6-1

x = 5
y = 1


d)y/2+x/4-1/5(x+2)=1,1
x-2y+4=x/2+3/4(y-0,5)

y/2+x/4-1/5x-2/5=1,1 /*20
x-2y+4 = x/2+3/4y-3/8 /*8

10y+5x-4x-8 = 22
8x-16y+32 = 4x+6y-3

10y+x = 30
-22y+4x = -35

x = 30-10y
-22y+4*(30-10y) = -35

-22y+120-40y = -35
x = 30-10y

-62y = -155
x = 30-10y

y = -2,5
x = 30-10y

x = 30-10*(-2,5)
y = -2,5

x = 55
y = -2,5

7 4 7
2010-03-22T19:15:48+01:00
A)6(x+y)=10y
y-x=0,5

6x+6y=10y
-x+y=0,5 /*6

6x-4y=0
-6x+6y=3
+____________
2y=3 /:2
y=2/3

y=2/3
6x+6y=10y

y=2/3
6x=4y

y=2/3
6x= 8/3 /:6

x=4/9
y=2/3
b)10(y+2)+3(x-5)=x-5
25(y+2)+3(x-5)=-10

10y+20+3x-15=x-5
25y+50+3x-15=-10

3x-x+10y=-5-20+15
3x+25y=-10-50+15

2x+10y=-10 /*(-3)
3x+25y= -45 /*2

-6x-30y=30
6x+50y=-90
+_________
20y= 60 /:20
y= 3
y=3
2x+10y=-10

y=3
2x+30=-10

y=3
2x=-40 /:(-2)

x=-20
y=3
c)2(2x-y)+3(x+3y)=42
5(x+3y)-8(2x-y)=-32

4x-2y+3x+9y=42
5x+15y-16x+8y=-32

7x+7y=42 /*11
-11x+23y=-32 /*7

77x+77y=462
-77x+161y=-224
+______________
238x= 238 /:238
x= 1
x=1
7x+7y=42

x=1
7+7y=42

x=1
7y=35 /:7

x=1
y=5
d)y/2+x/4-1/5(x+2)=1,1
x-2y+4=x/2+3/4(y-0,5)

y/2+x/4-1/5x-2/5=1,1 /*20
x-2y+4 = x/2+3/4y-3/8 /*8

10y+5x-4x-8 = 22
8x-16y+32 = 4x+6y-3

10y+x = 30
-22y+4x = -35

x = 30-10y
-22y+ 4*(30-10y) = -35

x=30-10y
-22y+120-40y = -35

x=30-10y
-62y = -155

x = 30-10y
y = -2,5

x = 30+25
y = -2,5

x = 55
y = -2,5

Mam nadzieje, że pomogłam
Pozdrawiam:-) !!!!
2 5 2